2007
DOI: 10.1080/03014220709510085
|View full text |Cite
|
Sign up to set email alerts
|

Frequency distribution and environmental correlates of plumage polymorphism in the grey fantailRhipidura fuliginosa

Abstract: The grey fantail (Rhipidura fuliginosa)in New Zealand displays a striking plumage polymorphism. Some individuals are coloured almost entirely black (the "black morph"), while other individuals sport a contrasting brown and white plumage (the "pied morph"). The adaptive significance of plumage polymorphism in this species is unknown. We mapped the relative distribution and frequency of each morph across the entire South Island range of the fantail, and correlated the frequency of the morphs with a variety of ec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…These patterns have been viewed as implying that there is an important selective advantage for the colour morphs or the genes associated with different morphs in the different areas (O'Donald ). For bird species, the adaptive significance of different morphs is poorly understood, although a few studies have demonstrated links between these clines and potential drivers such as environmental variables (Wunderle ), whereas others have failed to find any such relationships (Galeotti & Cesaris , Atkinson & Briskie ). Identifying the environmental patterns associated with these ratio‐clines may therefore be useful for indicating the selective forces operating on the balancing mechanisms of the different morphs (Galeotti et al .…”
mentioning
confidence: 99%
“…These patterns have been viewed as implying that there is an important selective advantage for the colour morphs or the genes associated with different morphs in the different areas (O'Donald ). For bird species, the adaptive significance of different morphs is poorly understood, although a few studies have demonstrated links between these clines and potential drivers such as environmental variables (Wunderle ), whereas others have failed to find any such relationships (Galeotti & Cesaris , Atkinson & Briskie ). Identifying the environmental patterns associated with these ratio‐clines may therefore be useful for indicating the selective forces operating on the balancing mechanisms of the different morphs (Galeotti et al .…”
mentioning
confidence: 99%
“…Interestingly, we found a morph-ratio cline in egg color ratios; that is, the proportion of white eggs in a population dramatically decreased at lower latitudes. Morph-ratio clines have been observed frequently in birds with polymorphic appearances (Wunderle, 1981;Atkinson and Briskie, 2007) but no such cases have been reported with repect to egg colors. Our results are therefore the first showing the presence of a morph-ratio cline in polymorphic egg colors of birds.…”
Section: Latitudinal Gradient In Egg Color Ratiosmentioning
confidence: 99%